Free trade agreements - Australia. Department of Foreign Affairs and Trade (Canberra : Department of Foreign Affairs and Trade, 2005)
Government web site containing information on current and planned free trade agreements with other nations. Contains full text of the agreements, reports, newsletters, submissions and media statements.
Title from title screen (viewed on 10 October 2005).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.fta.gov.au
Selected for archiving
Keywords: Free trade -- Australia; International trade -- Australia; Australia -- Commerce -- New Zealand; Australia -- Commerce -- Singapore; Australia -- Commerce -- Thailand; Australia -- Commerce -- United States